Teachers and Learning: Efforts to Develop Students' Character - Uri, Fatimah; Chanifuddin, Chanifuddin (Widyagogik, 2024)
A teacher is a person who is crucial in helping students develop the moral character, knowledge, and keterampilan that they need to achieve success in the future. Effective learning does not only focus on cognitive aspects, but also on developing students' character so that they become quality individuals, have good ethics, and are able to contribute positively to society. In this research, various literature related to educational theories, learning approaches, and character concepts are used as the basis for identifying strategies that can be applied by teachers in an effort to shape student character. Based on a literature review, it was found that the integration of character values in daily learning activities, the application of experience-based learning models, as well as humanist and participatory learning approaches, have great potential in forming students' strong character and integrity. It is hoped that this research can provide insight for educators and policy makers in formulating a more effective approach in developing student character in the educational environment.